Enhanced photocatalytic activities of net-like hematite nanoparticle/graphene oxide composite. Issue 4 (12th December 2014) - Zhang, Huanming; Zhu, Chunling; Chen, Yujin; Yang, Min; Yang, Piaoping; Wu, Xiaohong; Qi, Lihong; Meng, Fanna
Abstract : Net-like hematite nanoparticle/graphene oxide composite, in which the degree of oxidization of graphene oxide can be controlled by simply tuning annealing time, exhibits a high photocatalytic performance for water splitting. Abstract : A facile strategy was developed to fabricate net-like hematite nanoparticle/graphene oxide (GO) composite (NHG), in which the degree of oxidization of GO could be controlled by simply changing annealing time. NHG with GO of appropriate oxidization degree and content exhibited much higher photocatalytic activities than α-Fe2 O3 nanorods and commercial α-Fe2 O3 .